2006
DOI: 10.1097/00001665-200607000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Numerical Simulation in Maxillo-Facial Virtual Surgery (VISU)

Abstract: Computer-based surgery simulation is a rapidly emerging and increasingly important area of research that combines a number of disciplines for the common purpose of improving healthcare. The objective of this paper is to provide a virtual surgery (VISU) tool for accurately planning the aesthetic impact of hard and soft tissue movements in dento-skeletal malocclusions. The approach proposed here allows direct interaction with a completely three-dimensional (3-D) computed tomography (CT) model of a solid, highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 6 publications
0
32
0
2
Order By: Relevance
“…The results indicate that the preview with SurgiCase-CMF 1 software was of a higher quality than that obtained in a previous trial with VISU 13 (VISU 80%; SurgiCase-CMF 1 91%). Both soft tissue simulation software systems are based on the algorithm previously described 17 , so the difference in reliability is probably due to the more accurate surface reconstruction of hard tissues and the realism and precision of the surgical planning functions with SurgiCase-CMF 1 .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The results indicate that the preview with SurgiCase-CMF 1 software was of a higher quality than that obtained in a previous trial with VISU 13 (VISU 80%; SurgiCase-CMF 1 91%). Both soft tissue simulation software systems are based on the algorithm previously described 17 , so the difference in reliability is probably due to the more accurate surface reconstruction of hard tissues and the realism and precision of the surgical planning functions with SurgiCase-CMF 1 .…”
Section: Discussionmentioning
confidence: 50%
“…MARCHETTI et al 13 in a clinical and surgical study reported a reliability and reproducibility rate of 80% using VISU software. The Belgian company, Materialise, has developed a simulation software package, SurgiCase-CMF 1 , that includes VISU soft tissue simulation algorithms.…”
mentioning
confidence: 99%
“…Three-dimensional virtual reconstructions have recently been used for planning mandibular reconstruction [21], modeling of the orbital cavity [22], and in maxillo-facial surgery [23,24]. They are also widely used in paleoanthropological research [25][26][27][28], which illuminates the great potential of the new three-dimensional technologies.…”
Section: Introductionmentioning
confidence: 99%
“…These data can be converted into 3D images of a patient's craniofacial skeleton and the soft tissue covering it by using a sequence of computerized mathematical algorithms [1]. It is also possible to interact with these 3D images simulating the surgery that will take place and provides information about the surgical outcome predictions in soft and hard tissues.…”
Section: D Virtual Imagingmentioning
confidence: 99%